Pemanfaatan sari buah nanas dan air nira fermentasi sebagai perangkap pengganti feromon pada lahan kelapa sawit (Elaeis guineesis Jacq) - Mantep barokah; Aulia Rahmawati (Fakultas Pertanian Universitas Majalengka, 2024)
Palm oil is an important plantation commodity for Indonesia with its strategic role in Indonesia's economic development. Problems that occur in oil palm plantations are pest attacks such as the horn beetle (Oryctes rhinoceros). The large number of pest attacks can reduce plant productivity. This research aims to evaluate the effectiveness of pineapple juice and fermented sap as a substitute for chemical pheromones in ferrotrap traps to control horn beetle pests organically. The implementation will be carried out on agricultural land in Teluk Panji IV Village, Kampung Rakyat District, South Labuhan Batu Regency, North Sumatra in March 2024. The treatment used is natural pheromone material in the form of pineapple juice and fermented palm juice at 6 levels. The results showed that treatment with a mixture of 1 kg of pineapple juice and 1 liter of fermented juice (N5) was most effective on the variable number of horn beetles caught, was 138 individuals with an average of 19.7 individuals per day. This effectiveness is due to the volatile compounds in pineapple juice which attract horn beetles, as well as sap juice which strengthens the aroma. The results of research on the variable number of horn beetles that died on the most effective device used treatment of 1 kg of pineapple and 0.5 liters of sap (N4), was 8 horn beetles. This research indicated that the use of this natural material can be an environmentally friendly and economical alternative for controlling horn beetle pests in palm oil plantations